(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents the role of pedagogical technologies in increasing the efficiency of the educational process. In teaching the science of plant nutrition and fertilizers, technologies associated with the cooperation of students working in groups give predominantly good results in lectures, seminars, practical exercises, laboratory exercises on Venn diagram, “You are the owner of the earth.” ", "Save the Soil", "Soil-Plant-Fertilizer", "Zig-Zag", "Fish Skeleton", "Charkpalak", "Concept Analysis", Using methods such as "Cluster", "If I", “Flash”, “Boomerang”, “Colored Sticks”, “Fan”, “Brainstorm” allow you to interest the student, focus his attention, speed up the thought process and facilitate learning. It is advisable to use an organizer and technology. Organizing the educational process taking into account pedagogical features increases the effectiveness of the lesson, saves time and guarantees the achievement of the expected result.